Food authentication: state of the art and prospects - Danezis, Georgios P; Tsagkaris, Aristidis S; Brusic, Vladimir; Georgiou, Constantinos A (Current Opinion in Food Science, 2016)
Food authentication is analytical process that validates label information about the food origin and production process. This review discusses emerging food authenticity indicators including rare earth elements, metabolic profiles, sensory profile evaluation, and microbial fingerprinting. A scientometric evaluation that highlights research trends and emerging approaches of this evolving field is presented. We analyzed and provided an insight into most commonly studied food types and drinks and highlighted the most promising authenticity markers for each major group. Finally, we discussed the data explosion that is emerging and discussed the developing trends in the field. The future of food authentication lies in Big Data since we are already collecting and analyzing huge amounts of data that converge from multiple sources. Big Data Analytics will include standardization of experiments, study design workflows, and of data reporting. Emerging data analytical tools will include integration of geographic information systems with climate information systems and metabolomics databases for precise spatio-temporal identification of food origin.